2015
DOI: 10.1103/physrevb.91.054409
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-two-dimensionalS=12magnetism ofCu[C6H2(<

Abstract: We report structural and magnetic properties of the spin- square lattice with the ratio of the couplings Ja/Jc 0.7 along the a and c directions, respectively. No clear signatures of the long-range magnetic order are seen in thermodynamic measurements down to 1.8 K. However, the gradual broadening of the ESR line suggests that magnetic ordering occurs at lower temperatures. Leading magnetic couplings are mediated by the organic anion of the pyromellitic acid and exhibit a nontrivial dependence on the Cu-Cu dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
(26 reference statements)
3
20
0
Order By: Relevance
“…(a) (b) Similarly, it was shown in reference [79], that the susceptibility and isothermal magnetization of Cu(PM)(EA)2 (PM = [C6H2(COO)4] 4− , EA = [C2H5NH3] + ) can be described by the model (Equation (4)) with various R in a wide range of temperatures and magnetic fields ( Figure 5). Similarly, it was shown in reference [79], that the susceptibility and isothermal magnetization of Cu(PM)(EA) 2 (PM = [C 6 H 2 (COO) 4 ] 4− , EA = [C 2 H 5 NH 3 ] + ) can be described by the model (Equation (4)) with various R in a wide range of temperatures and magnetic fields ( Figure 5). in further analysis as was demonstrated in the analysis of the susceptibility of Cu(NCS)2 where the first-principle calculations enabled to identify the material as the realization of the rectangular lattice with J/kB ≈ 170 K and R ≈ 0.08 [78].…”
Section: The S = 1/2 Heisenberg Antiferromagnet On the Spatially Anissupporting
confidence: 59%
See 2 more Smart Citations
“…(a) (b) Similarly, it was shown in reference [79], that the susceptibility and isothermal magnetization of Cu(PM)(EA)2 (PM = [C6H2(COO)4] 4− , EA = [C2H5NH3] + ) can be described by the model (Equation (4)) with various R in a wide range of temperatures and magnetic fields ( Figure 5). Similarly, it was shown in reference [79], that the susceptibility and isothermal magnetization of Cu(PM)(EA) 2 (PM = [C 6 H 2 (COO) 4 ] 4− , EA = [C 2 H 5 NH 3 ] + ) can be described by the model (Equation (4)) with various R in a wide range of temperatures and magnetic fields ( Figure 5). in further analysis as was demonstrated in the analysis of the susceptibility of Cu(NCS)2 where the first-principle calculations enabled to identify the material as the realization of the rectangular lattice with J/kB ≈ 170 K and R ≈ 0.08 [78].…”
Section: The S = 1/2 Heisenberg Antiferromagnet On the Spatially Anissupporting
confidence: 59%
“…(a) (b) Similarly, it was shown in reference [79], that the susceptibility and isothermal magnetization of Cu(PM)(EA)2 (PM = [C6H2(COO)4] 4− , EA = [C2H5NH3] + ) can be described by the model (Equation (4)) with various R in a wide range of temperatures and magnetic fields ( Figure 5). Apparently, using proper parameters, various theoretical predictions yield identical behavior for both, susceptibility and magnetization [79]. Thus, making conclusions on the basis of magnetic data only, can be very tricky, since the height of the maximum, χ max , as well as its position, T max , depend on the J and g-factor values.…”
Section: The S = 1/2 Heisenberg Antiferromagnet On the Spatially Anissupporting
confidence: 59%
See 1 more Smart Citation
“…18,19 We have recently demonstrated that the organic moieties can modulate both the structural and magnetic features between metal ions significantly as the organic ligand NIPA leads to the formation of a hourglass nanomagnet Cu 5 (NIPA) 4 (OH) 2 .11H 2 O with two antiferromagnetic (AFM) and one ferromagnetic (FM) couplings between Cu 2+ ions 20 while another similar ligand leads to the formation of a quasi-two-dimensional (2D) AFM with weakly anisotropic spin-1/2 square lattice. 21 Cu(1,3-bdc) is another well studied compound where Cu 2+ ions are connected via IPA forming a perfect Kagomé lattice with strong magnetic frustration. 22 It undergoes a magnetic long-range-order (LRO) at T N 1.77 K. We have reported that in such Kagomé lattices by changing the ligand it is possible to tune the magnetic ground state keeping the crystal structure intact.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of corresponding theoretical predictions and difficulties with preparation of such materials did not allow finding proper experimental realizations. A few realizations of SASL with spin 1/2 appeared only recently [4,5].…”
Section: Introductionmentioning
confidence: 99%